Crude oils as ore fluids: An experimental in-situ XAS study of gold partitioning between brine and organic fluid from 25 to 250 °C. (1st January 2019) - Crede, Lars-S.; Liu, Weihua; Evans, Katy A.; Rempel, Kirsten U.; Testemale, Denis; Brugger, Joël
Abstract: Organic matter can be associated with mineralization in hydrothermal ore deposits. One hypothesis is that this organic matter represents remnants of organic fluids (crude oils) that were competing with aqueous fluids for metal transport and contributed to metal endowment. We investigated the transport of gold (Au) in model oil compounds (S-free n -dodecane, CH3 (CH2 )10 CH3, DD; and S-bearing 1-dodecanethiol, CH3 (CH2 )10 CH2 SH; DDT) from 25 °C to 250 °C using in-situ synchrotron X-ray absorption spectroscopy (XAS) experiments to determine the speciation and the structural properties of gold complexes in the aqueous- and oil-based fluids. For most experiments, DD or DDT were in contact with Au-bearing acidified water, or acidified water plus 10 wt% NaCl (pH25°C = 1.85 in both cases). Gold rapidly partitioned from the aqueous phase into DD and DDT. Below 125 °C, Au(III)Cl is dominant in the DD and the adjacent water with a refined coordination number (CN) of chloride of 4.0(3) and an AuCl bond length of 2.28 Å, consistent with the tetrachloroaurate complex (AuCl4 − ) being stable in both the aqueous and organic phases. In contrast, Au(III) is rapidly reduced in the presence of DDT and an Au(I) complex dominates in both water and adjacent DDT with a CN of sulfur ∼2.0, suggesting a [RS-Au-SR] − (RS = DDT with deprotonated thiol group) complex with AuS bond lengths ranging from 2.29(1) Å to 2.31(3) Å. In an open system of DDT in contact with water, of which the water and DDT were analyzed separately, AuCl4 − was dominant in the water phase, and Au(RS)2 − dominant in DDT, possibly due to different equilibration kinetics in the beaker and glassy carbon tube. Since sulfur and organothiol compounds are ubiquitous and abundant components in natural oils, this study demonstrates the potential of natural oils to scavenge and enrich gold from co-existing gold-bearing brines. In particular, Au(I) organothiol complexes may contribute to transport in low-temperature (<125 °C) ore fluids such as those in basinal environments – in both hydrothermal fluids and oils. At temperatures ≥125 °C, gold was reduced to metallic gold in all experiments, suggesting that organo-stabilized nanoparticles may be the major form of gold to be scavenged, concentrated or transported in crude oils at these conditions. The results imply that brine-oil interactions may enrich Au in oils, and that oils may be an effective ore fluid in sedimentary environments.